Development of an Interactive Multimedia-Based IIMSE Learning Model: Accounting Learning - Tampubolon, Dayana Rebecca; Napitupulu, Efendi; Tambunan, Hamonangan (Randwick International of Education and Linguistics Science Journal, 2024)
The purpose of this study is to ascertain whether the interactive multimedia-based IIMSE learning paradigm is feasible and beneficial for teaching accounting to students in class XI at Budisatrya Private Vocational School in Medan. This kind of research uses the ASSURE model in conjunction with R&D product creation. Based on the validation of learning material experts (86.4%), learning design experts (88.1%), and media experts (90.6%), who all fall into the very feasible category, the research's findings indicate that the interactive multimedia-based IIMSE learning model is appropriate for use. Field trials came in at 85.6%, small group trials came in at 81.7%, and individual trials came in at 77.1%, all falling into the extremely feasible category. The hypothesis submission results demonstrate that the interactive multimedia-based IIMSE learning model is appropriate for use in accounting courses and that the learning outcomes of students treated with the interactive multimedia-based IIMSE learning model differ significantly from those of students treated with the conventional learning model. This is demonstrated by the data processing findings, which show that tcount > ttable (5.63>1.63) at the significance level α = 0.05 with df obtained t table = 50. We can conclude that there are disparities in the learning results before and after therapy, with Ho being rejected and Ha being accepted. As a result, student learning outcomes are improved by the IIMSE learning paradigm, which is based on interactive multimedia in accounting education.